Non-interacting, Non-opioid, and Non-barbiturate Containing Acute Medication Combinations in Headache: A Pilot Combinatorics Approach Based on DrugBank Database - Kaytser, Victor; Zhang, Pengfei (Frontiers in Neurology, 2021)
Structured Abstract Background: Polypharmacy in abortive medications is often inevitable for patients with refractory headaches. Objective: We seek to enumerate an exhaustive list of headaches abortive medications that are without drug-drug interactions. Methods: We updated a list of acute medications based on the widely used Jefferson Headache Manual with novel abortive medications including ubrogepant, lasmiditan, and rimegepant. Opioids and barbiturate-containing products are excluded. From this resultant list of medications (Table 1), we then conducted an exhaustive search of all pair-wise interactions via DrugBank’s API. Using this interaction list, we filtered all possible two, three, and four drug combinations of abortive medications. The list of medications (Table 1) was then reapplied to DrugBank to verify the lack of known drug-drug interactions. Results: There are 192 medication combinations that do not contain any drug-drug interactions. Most common elements in these combinations are ubrogepant, prochlorperazine, followed by tizanidine. There are 67 three-drug combinations that do not contain interactions. Only 2 of the four-drug combinations do not yield some form of drug-drug interactions. Conclusion: This list of headaches abortive medications without drug-drug interactions is a useful tool for clinicians seeking to more effectively manage refractory headaches by implementing a rational polypharmacy.